Tathwiiru Mawaad Ta'liim Al-Lughah Al'Arabiyah fil Ma'aahid As-Salafiyah Min Mandhuuri Mu'aayiri Muhtawa Manhaj Ta'liim Al-Lughah Al'Arabiyah lin Naathiqiina Bighairiha - Ahmad Ubaedi Fathuddin (Arabic Education Program IAIN Pekalongan, 2015)
Arabic learning material in Islamic Boarding School has not developed well and it still relies on Nahwu as the only benchmark of success in learning Arabic. In fact, the students’ need in learning Arabic is not only about how to read and understand kitab kuning (classic book), but also how to speak and write in Arabic. Therefore, it is necessary to revise the learning material of Arabic language in Islamic Boarding School. The aim of this study is to describe the efforts of revising the Arabic learning material in Islamic Boarding School in order to find an interface between the previous learning material and the principles of Arabic learning material compilation. This study uses qualitative approach. The data was collected by using interview, observation, and documentation. The collected data was then analyzed by using triangulation. The research result shows that Arabic learning material should consist of three language competence; they are aspect of language, aspect of culture, and language function as a means of communication.